2002
DOI: 10.1002/agr.10035
|View full text |Cite
|
Sign up to set email alerts
|

The white shrimp futures market: Lessons in contract design and marketing

Abstract: The successful introduction of futures contracts to industries unfamiliar with futures markets is likely to become increasingly important as futures exchanges move to alternative governance structures (e.g., for-profit corporations), trading platforms evolve (i.e., electronic|Internet trading), and regulatory requirements relax. Here, we examine the performance of the Minneapolis Grain Exchange's white shrimp futures contract, one of the first futures contracts aimed at the aquaculture industry. Although the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“… Cash market prices fluctuate and/or are uncertain (Maliaris 2000; Sanders and Manfredo, 2002;Telser, 1981).…”
Section: Specific Characteristics Of Commoditiesmentioning
confidence: 99%
“… Cash market prices fluctuate and/or are uncertain (Maliaris 2000; Sanders and Manfredo, 2002;Telser, 1981).…”
Section: Specific Characteristics Of Commoditiesmentioning
confidence: 99%
“…() argue that the activeness of a commodity's cash market (and the price information revealed through active cash markets) is a necessary condition for a successful futures market. Research into the failures of the stocker cattle futures contract (Perversi et al., ) and the white shrimp contract (Sanders and Manfredo, ) shows that low basis volatility and market participants’ general knowledge of futures markets are also important. Evaluations of potential salmon (Bergfjord, ) and Brazilian milk (Siqueira et al., ) futures contracts concluded that product homogeneity, high price risk, and the absence of competing risk‐management tools were among the factors contributing to the viability of futures markets.…”
Section: Determinants Of Futures Contract Success As Identified By Thmentioning
confidence: 99%
“…Studies have also suggested that the types of futures market participants can impact a contract's trade volume. For example, Sanders and Manfredo () and Bollman et al. () hypothesize that the failures of the white shrimp and diammonium phosphate futures contracts, respectively, were related to the markets’ inability to attract speculative trade.…”
Section: Empirical Model For Evaluating Futures Contract Successmentioning
confidence: 99%
“…The plywood futures resulted in the establishment of a Research and Development department in the exchange. Sanders and Manfredo (2002) examined the performance of the Minneapolis Grain Exchange's white shrimp futures contract, one of the first futures contracts aimed at the aquaculture industry. Although the market structure largely conformed to the traditional criteria for a successful futures market, the contract's performance was disappointing in terms of liquidity, basis behavior and hedging effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%